Adult Attachment and Personal, Social, and Symptomatic Recovery From Psychosis: Systematic Review and Meta-Analysis - van Bussel, E. M. M.; Nguyen, N. H. M.; Wierdsma, A. I.; van Aken, B. C.; Willems, I. E. M. G.; Mulder, C. L. (Frontiers in Psychiatry, 2021)
Despite growing evidence for the role of attachment in psychosis, no quantitative review has yet been published on the relationship in this population between insecure attachment and recovery in a broad sense. We therefore used meta-analytic techniques to systematically appraise studies on the relationship between attachment and symptomatic, social and personal recovery in clients with a psychotic disorder. Using the keywords attachment, psychosis, recovery and related terms, we searched six databases: Embase, Medline Epub (OVID), Psycinfo (OVID), Cochrane Central (trials), Web of Science and Google Scholar. This yielded 28 studies assessing the associations between adult attachment and recovery outcome in populations with a psychotic disorder. The findings indicated that insecure anxious and avoidant attachment are both associated with less symptomatic recovery (positive and general symptoms), and worse social and personal recovery outcomes in individuals diagnosed with a psychotic disorder. The associations were stronger for social and personal recovery than for symptomatic recovery. Attachment style is a clinically relevant construct in relation to the development and course of psychosis and recovery from it. Greater attention to the relationship between attachment and the broad scope of recovery (symptomatic, social and personal) will improve our understanding of the illness and efficacy of treatment for this population.